Passenger Satisfaction on The Services Provided by Halim Perdana Kusuma Airport Jakarta in 2014 - Andri, Andri Andri; Kosasih, Suparwan Cecep; Haryono, Haryono Haryono (STMT Trisakti, 2015)
Halim Perdana Kusuma International Airport, which is integrated with the development of National Economic Zones, is included in the implementation of Master Plan for the Acceleration and Expansion of Indonesian Economic Development in Java and Sumatra islands. The operation of Halim Perdana Kusuma Airport is expected to become a locomotive for the economy of its surrounding regions. Therefore, its presence will encourage the emergence of centers of growth and new economic activities. The operation of Halim Perdana Kusuma airport signifies the seriousness of the Indonesian government in preparing the accelerated development of national connectivity and supporting infrastructures in order to support the trade connectivity and the projected national and regional aviation hub. Service is an act, performance appearance, intangible and it quickly disappears, which can only be consumed but can not be held, where customers can participate more actively in the process of consuming it. In this case, customer assessment on the performance ofservice providers will greatly influence the passenger satisfaction, in which passengers who have a level of importance or high expectations here to get performance comparable airports of giving the passenger satisfaction. Passenger satisfaction will have a positive impact on the airport, while the airport sales volume will likely increase if the passengersâ past experience as well as its word of mouth are positive.